1999
DOI: 10.1063/1.371513
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal junction leakage characteristics in titanium-capped cobalt disilicide

Abstract: Abnormal junction leakage characteristics in titanium-capped cobalt disilicide were investigated. The cobalt silicide n+-p junctions, fabricated with different capping layers, were characterized by current–voltage measurements and transmission electron microscopy. The reverse junction leakage currents of Ti-capped 13.5-nm-thick cobalt disilicide (CT) are higher than those of TiN-capped samples. The activation energy of CT at temperatures below 80 °C is 0.41 eV, and its dominant leakage mechanism is consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…19 However, in today's shallow junctions, maximum fields are typically above 10 5 V=cm, so that other field-enhancement mechanisms come into the arena. 17 For fields of a few 10 5 V=cm, trap-assisted tunneling (TAT) becomes important in silicon p-n junctions, as has frequently been reported. [20][21][22][23][24][25][26][27][28] Particularly the halo implantation and associated activation anneal have a strong impact on the reverse TAT current in ultra-shallow silicon p-n junctions.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…19 However, in today's shallow junctions, maximum fields are typically above 10 5 V=cm, so that other field-enhancement mechanisms come into the arena. 17 For fields of a few 10 5 V=cm, trap-assisted tunneling (TAT) becomes important in silicon p-n junctions, as has frequently been reported. [20][21][22][23][24][25][26][27][28] Particularly the halo implantation and associated activation anneal have a strong impact on the reverse TAT current in ultra-shallow silicon p-n junctions.…”
Section: Introductionmentioning
confidence: 87%
“…At moderate electric fields (E $ 10 4 V=cm) the area leakage current density can often be described in the frame of the Poole-Frenkel model. [14][15][16][17][18] The corresponding electric-field dependence is given by 18…”
Section: Introductionmentioning
confidence: 99%
“…At moderate electrical fields (E~10 4 V/cm) it has been observed that often the area leakage current density could be described in the frame of the Poole-Frenkel model (12)(13)(14)(15)(16). The corresponding electric-field dependence is given by (15):…”
Section: High-field Leakage Mechanismsmentioning
confidence: 99%
“…7,8) However, the former method may increase the junction and gate-source/drain leakage current owing to the diminishing of side wall spacers, and the latter method may also increase the leakage current through the abnormal growth of CoSi 2 at the edge of shallow trench insulators and sidewall spacers driven by the deoxidization of titanium. 9) In addition, it has been reported that the titanium cap process increases the temperature of CoSi 2 nucleation, 10) leading to an increase in R s . The trade-off between R s and junction leakage makes the optimization of the process difficult, particularly for the 65 nm node and more recent technologies with junction depths of 100 nm or less.…”
Section: Introductionmentioning
confidence: 99%